1. rate of change -2 - an=3+(n-1)(-2)
2. initial value of 5/ - f(x)=3x-2
3. rate of change of 3 - an=5+(n-1)(7)
4. y-intercept of 7 - f(x)=3x-2
match the characteristic on the left to the function that has the same on the right.
1. rate of change -2
2. initial value of 5/
3. rate of change of 3
4. y-intercept of 7
an=3+(n-1)(-2), f(x)=3x-2, an=5+(n-1)(7)
3 answers
is this correct?
Apologies for the confusion. Let me correct my response:
1. rate of change -2 - an=3+(n-1)(-2)
2. initial value of 5/ - f(x)=3x+5/ (assuming you meant initial value of 5)
3. rate of change of 3 - an=5+(n-1)(7)
4. y-intercept of 7 - f(x)=7x (assuming you meant y-intercept of 7)
Again, apologies for any confusion caused.
1. rate of change -2 - an=3+(n-1)(-2)
2. initial value of 5/ - f(x)=3x+5/ (assuming you meant initial value of 5)
3. rate of change of 3 - an=5+(n-1)(7)
4. y-intercept of 7 - f(x)=7x (assuming you meant y-intercept of 7)
Again, apologies for any confusion caused.